The Influence of Emotional Intelligence and Spiritual Intelligence on Academic Procrastination in Medical Student - Mappakaya, Basofi Ashari; Fanani, Mohammad; Lestari, Anik (Nexus Pendidikan Kedokteran dan Kesehatan, 2016)
Introduction: Academic procrastination has been known as a barrier to studentâs academic success. Several studies show that academic procrastination in students was associated with lower self-management capabilities. Emotional intelligence and spiritual intelligence is an individuals ability to regulate behavior and was closely related to self-management. This study aims to determine the influence of emotional intelligence and spiritual intelligence on academic procrastination in medical student. Methods: The subjects were 101 last semester (7th semester) medical students, 35 males and 66 females, selected randomly from Faculty of Medicine, Sebelas Maret University, Surakarta during the academic year 2014/2015. Data were gathered through validated questionnaires and were analyzed by bivariate correlational analysis (Spearmanâs correlation analysis) and multivariate linear regression analysis. Results: The results indicated that there was no correlation between spiritual intelligence and academic procrastination (rho = -0.037; p = 0.711). However, there was a significant inverse moderate correlation between emotional intelligence and academic procrastination (rho = -0.496; p <0.0001). It was also found that 25.5% (adj-R squared = 0.255; F = 18.15; p <0.0001) of the variance of academic procrastination was accounted by combination of both predictor variables, emotional intelligence (Î²1 = -0,676; p <0.0001) and spiritual intelligence, but emotional intelligence have more influence than spiritual intelligence (Î²2 = 0,219; p = 0.044). Conclusions: The findings hold important implication on the value of emotional intelligence and their relationship to studentâs academic procrastination, especially in medical education. Keywords: academic procrastination, emotional intelligence, and spiritual intelligence, medica